Surface behavior of ceramides with very long chain polyunsaturated fatty acids - Peñalva, Daniel Alejandro (2012)
Molecular species of sphingomyelin (SM) and ceramide (Cer) with nonhydroxy and 2-hydroxy very long-chain (C24 to C36) polyunsaturated fatty acids (VLCPUFA) abound in mammalian spermatogenic cells and spermatozoa. In rat sperm, Cer naturally occurs in the tail and is produced from SM in the head once the acrosomal reaction is completed. The properties these atypical lipids confer to membranes remain to be defined. The aim of this study was to evaluate surface properties of isolated molecular species of Cer in monolayers. Ceramides containing nonhydroxy and 2-hydroxy fatty acids like 28:4, 30:5 and 32:5 isolated from rat testes, were resolved by a combination of chromatographic techniques including HPLC. Langmuir monolayer studies allowed to measure surface pressure, surface potential and reflectivity images by Brewster angle microscopy of these Cer spread at the air-water interface. We were able to determine average molecular area (degree of packing), surface potential, and thickness of these films. Isotherms of these molecular species showed expanded phases at large molecular areas and in-plane phase transitions to a liquid condensed state at lower molecular areas at both 7°C and 21°C. In the transition region, the formation of domains with different shapes could be appreciated. Our results show that ceramide surface properties depend on fatty acid unsaturation, chain length and the presence of the 2-hydroxyl group in the acyl chain. Furthermore, most of these properties differed significantly from those of previously characterized Cer with long-chain saturated fatty acids.